The Authority of Electronic Evidence before the Administrative Judiciary: A Comparative Study (International Journal of Financial, Administrative and Economic Sciences, 2024)
This research comes as part and introduction to a master’s thesis in public law at King Abdulaziz University entitled “The Validity of Electronic Evidence before the Administrative Judiciary a Comparative Study by researcher Saeed Alghamdi and supervised by Associate Professor of Administrative Law, Dr. Alaa El Din Mohammed. There is no doubt that modern means of proof, especially those that are done via the Internet, are important in our contemporary society, what is called digital evidence, and due to the importance of digital evidence in proof, the research addressed the answer to the problem: To what extent is electronic evidence authoritative before the administrative judiciary? Many questions arise from it that do not go beyond this problem in their content. The researcher followed the comparative approach to answer the research question, as a comparison will be made between the Egyptian, Emirati and Saudi laws, and the researcher reached a number of results, the most important of which is that electronic evidence is considered independent evidence and has strong authoritativeness before the judiciary because the Saudi evidence system included electronic evidence as independent evidence and became like other evidence that is independent and it is valid to base the ruling on it and its provisions apply before the administrative judiciary by virtue of what is stipulated in the litigation system before the Saudi Board of Grievances. In light of the previous results, we recommend that the Saudi regulator add a paragraph in Article Nine of the Enforcement System stating that an electronic document authenticated electronically is considered an executive document.
Keywords: Evidence System; Electronic Evidence; Electronic Editor; Electronic Dealing; Administrative Judiciary